Modulation engineering of in situ cathodic activation of FePx based on W-incorporation for the hydrogen evolution reaction. Issue 23 (3rd June 2020) - Yang, Min; Zhu, Yu-Ran; Lin, Zhong-Yuan; Yan, Xin-Tong; Dong, Bin; Zhou, Ya-Nan; Li, Qing-Zhong; Zhou, Yu-Lu; Nan, Jun; Chai, Yong-Ming
Abstract : In situ electrochemical activation as a new pretreating method to adjust electrocatalytic performance attracts extensive attention. Abstract : In situ electrochemical activation as a new pretreating method to adjust electrocatalytic performance attracts extensive attention. However, the activation mechanisms of electrocatalysts are still ambiguous. Herein, we propose a facile modulation strategy of in situ cathodic activation of FeP x based on W-incorporation (W-FeP x /IF) for the hydrogen evolution reaction (HER). The activated W-FeO x with obvious surface reconstruction demonstrates the role of W-incorporation for driving the cathodic activation of FeP x, which suggests the larger surface area and more active sites. In fact, W incorporation can not only accelerate the cathodic activation process but also act as the adsorption sites for Had to form the synergistic effect with FeO x for water dissociation. The obtained W-FeO x /IF exhibits greatly enhanced HER activity featuring decreased overpotential from 237.7 to 154.0 mV at 100 mA cm −2, which may be ascribed to W-FeO x with double catalytic active sites after cathodic activation. Additionally, the modulation effects of cathodic activation can be exactly achieved by changing electrochemical parameters such as CV cycles. W-FeO x /IF also shows excellent long-term stability for at least 100 h at 100 mA cm −2 . This modulation engineering based on metal doping is expected to provide inspiration for the understanding of the cathodic activation process for efficient electrocatalysts.